2018
DOI: 10.1177/2280800017750359
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo assessment of biomedical Mg–Ca alloys for bone implant applications

Abstract: Background: Magnesium (Mg)-based alloys are considered to be promising materials for implant application due to their excellent biocompatibility, biodegradability, and mechanical properties close to bone. However, low corrosion resistance and fast degradation are limiting their application. Mg-Ca alloys have huge potential owing to a similar density to bone, good corrosion resistance, and as Mg is essential for Ca incorporation into bone. The objective of the present work is to determine the in vitro degradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 28 publications
(46 reference statements)
3
40
0
1
Order By: Relevance
“…These results were supported by data obtained during in vivo studies (Li et al, 2008). Makkar et al (2018) evaluated the in vitro performance of binary Mg-xCa alloys (0.5 wt% and 5.0 wt %) for use as biodegradable biomaterials within bone. The results showed a better behaviour for the Mg-0.5Ca alloy in comparison to the Mg-5.0Ca alloy, both in terms of biocompatibility and corrosion resistance, suggesting that the Mg-0.5Ca alloy could be used as a biodegradable base material for clinical applications.…”
Section: Mg-alloyssupporting
confidence: 54%
“…These results were supported by data obtained during in vivo studies (Li et al, 2008). Makkar et al (2018) evaluated the in vitro performance of binary Mg-xCa alloys (0.5 wt% and 5.0 wt %) for use as biodegradable biomaterials within bone. The results showed a better behaviour for the Mg-0.5Ca alloy in comparison to the Mg-5.0Ca alloy, both in terms of biocompatibility and corrosion resistance, suggesting that the Mg-0.5Ca alloy could be used as a biodegradable base material for clinical applications.…”
Section: Mg-alloyssupporting
confidence: 54%
“…The in vivo studies of Mg–Ca‐based alloys can be found in the literature . Erdmann et al evaluated the mechanical and degradation performance of Mg–0.8Ca screws by implanting them in the tibia bones of rabbits.…”
Section: Mg and Its Alloysmentioning
confidence: 99%
“…The time checkpoints were set as day 1, day 3, week 1, week 2, and week 3. The PBS solutions were refreshed every 2 days with 500 μL of a fresh solution using a method similar to that mentioned in refs (51) and (52). At the end of each interval, the concentration of Mg 2+ ions released into the extracted PBS solution was determined using inductively coupled plasma optical emission spectroscopy (ICP-OES 700, Agilent) after measuring the pH value of the extracted using a pH meter (Thermo Fisher Scientific) in each time checkpoints.…”
Section: Methodsmentioning
confidence: 99%